Low bit rate speech coders - Shah, Asadullah; Abdullah Zammarh, Nuha (IIUM Press, 2011)
A great number ofspeech coding has been developed in recent years and many others are in their advanced level of development. Most of these encoding algorithms use hybrid methodology of wavefonn coding and voice coding commonly knov.m as (vocoding). The speech quality ofthese coders is comparable with Pulse Code Modulation (PCM); a popular encoding technique used in digital telephony